Determinants of Academic Stress in Students - Nadia Rizki Azmi Harahap; Aip Badrujaman; Dede Rahmat Hidayat (Bisma The Journal of Counseling, 2022)
Students can experience academic stress at different levels, if the academic stress experienced by students increases, it will affect the productive quality of students in carrying out lectures both online and face-to-face, therefore it is necessary to study in depth related to the determining factors of student academic stress to help students deal with the challenges faced during lectures. The strategy used in this study is a type of systematic literature review research using qualitative methods. The approach used in this study is a meta-ethnograph, based on the results of research that students can experience academic stress both online and offline lectures, as for the determining factor of student academic stress, which is not only a factor from within the individual (internal), but can also be influenced by external factors (external). Internal factors are self-efficacy, hardiness, mindset, peer competition, character, changes in life atmosphere, difficulty managing life, low achievement motivation, low self-regulated learning, dependence on gadgets, self-adjustment and physical factors. External factors are low social support, financial problems, less supportive signals when studying online, the cost of spending internet credit increases. For future research, we can present a guidebook related to self-help to help students overcome academic stress.